Complexity in salt marsh circulation for a semienclosed basin. Issue 10 (2nd October 2015) - Sullivan, Jessica Chassereau; Torres, Raymond; Garrett, Alfred; Blanton, Jackson; Alexander, Clark; Robinson, Michael; Moore, Trent; Amft, Julie; Hayes, David
Abstract: The fine details of overmarsh circulation remain largely unexplored and yet they are typically assumed to control many attributes of salt marsh material cycling, transport, and accretion. We characterized the spatial and temporal variability in overmarsh circulation at a 2 km 2 Georgia, USA, salt marsh using field observations, dye tracer, and numerical simulations. The marsh bathymetry was created with a high‐precision Global Positioning System survey that details the geomorphic structure of intertidal creeks and salt marsh platform features greater than about 1 m in width. We assessed flow path dynamics at four spatial scales ranging from 1 m to 1000 m. Results show the development and decay of simultaneous flow divergence and convergence, concentrated flow and large‐scale rotational flow, and strong differences between flood and ebb pathways. This current complexity is set by submergence and emergence of subtle salt marsh platform geomorphic structure, and it highlights the role of topography in system‐wide flow processes. Key Points: Overmarsh flow complexity results from submergence‐emergence of topography Complexity occurs as simultaneous convergence, divergence and rotational flow High quality bathymetry is needed to accurately simulate overmarsh flow